Development of augmented reality and virtual reality learning media on human respiratory system material - Susilowati Susilowati; Hanum Mukti Rahayu; Mahwar Qurbaniah (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
The traditional learning media for the human respiratory system at SMA Mujahidin rely heavily on textbooks and Power Point presentations. To enhance this experience, we have developed Augmented Reality (AR) and Virtual Reality (VR) tools that feature realistic 3D animations. These immersive visualizations provide students with a more tangible and concrete understanding of respiratory anatomy and function. The purpose of this study is to create a flipbook learning medium that integrates AR and VR technologies, ensuring the content is both valid and practical for classroom use. We employed a Research and Development (R&D) approach, adapting Thiagarajan’s original 4D model into a streamlined 3D framework: Define, Design, and Develop. This methodology aims to deliver an engaging, effective learning tool that enhances students’ mastery of the human respiratory system. The data collection instruments included interview sheets, expert validation questionnaires, and student response questionnaires. Validation was carried out by three material experts, three media experts, and three language experts, with each obtaining a percentage of 92.37% for material experts, 95% for media experts, and 93.33% for language experts, indicating that the media is categorized as highly valid. The product trials were conducted in two stages: a small-scale trial involving 22 students (20% of the Grade XI population) and a large-scale trial involving 56 students (50% of the Grade XI population at SMA Mujahidin Pontianak). The results showed that the media received positive feedback, with student response rates of 84.95% in the small-scale trial and 82.6% in the large-scale trial. These findings indicate that the Augmented Reality and Virtual Reality-based learning media are feasibleAbstrak. Media pembelajaran pada materi sistem pernapasan manusia di SMA Mujahidin masih terbatas menggunakan buku paket dan power point. Untuk itu, media pembelajaran Augmented Reality dan Virtual Reality yang dikembangkan merupakan media yang menampilkan visualisasi animasi 3D tampak nyata, sehingga memberikan pemahaman siswa lebih konkret dalam belajar, khususnya materi sistem pernapasan manusia. Penelitian ini bertujuan untuk mengembangkan media pembelajaran flipbook berbasis Augmented Reality dan Virtual Reality pada materi sistem pernapasan manusia yang valid dan layak digunakan. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan model pengembangan 4D yang dikembangkan oleh Thiagarajan, namun dimodifikasi menjadi 3D (define, design, development). Validasi dilakukan oleh tiga validator ahli materi, tiga validator ahli media, dan tiga validator ahli bahasa dengan masing-masing memperoleh persentase sebesar 92,37% ahli materi, 95 % ahli media dan 93,33% ahli Bahasa yang menunjukan bahwa media tersebut dikategorikan sangat valid. Uji coba produk dilakukan dalam dua tahap, yaitu uji coba skala kecil terhadap 22 siswa (20% dari siswa kelas XI) dan uji skala besar terhadap 56 siswa (50% dari siswa kelas XI SMA Mujahidin Pontianak). Hasil uji coba menunjukkan bahwa media memperoleh tanggapan positif dengan persentase respon siswa sebesar 84,95% pada uji coba skala kecil dan 82,6% pada uji coba skala besar. Hasil tersebut menunjukkan bahwa media pembelajaran Augmented Reality dan Virtual Reality yang dikembangkan layak digunakan.